2021
DOI: 10.1016/j.cej.2020.126926
|View full text |Cite
|
Sign up to set email alerts
|

Engineered biochar – A sustainable solution for the removal of antibiotics from water

Abstract: Antibiotic contamination and the spread of antimicrobial resistant bacteria are global environmental issues. Given the growing consumption of antibiotics, it is crucial to reduce their presence in the environment. Adsorption is one of the most efficient methods for removing contaminants from water and wastewater. For this process to be effective, it is of key importance to identify adsorption mechanisms that allow an efficient and selective adsorbent to be chosen.Carbon-based materials (including activated car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(112 citation statements)
references
References 211 publications
0
93
0
Order By: Relevance
“…The use of palm oil residues as adsorbents is of special interest as the palm oil agro-industry generates a significant amount of residual biomass (~87 million t/y) [14]. Several studies have demonstrated that biochar produced from palm oil and other agro-industrial residues is an effective adsorbent for removing heavy metals [15][16][17], dyes [18,19], pharmaceuticals [20][21][22][23], and other organic pollutants [24] from aqueous systems.…”
Section: Introductionmentioning
confidence: 99%
“…The use of palm oil residues as adsorbents is of special interest as the palm oil agro-industry generates a significant amount of residual biomass (~87 million t/y) [14]. Several studies have demonstrated that biochar produced from palm oil and other agro-industrial residues is an effective adsorbent for removing heavy metals [15][16][17], dyes [18,19], pharmaceuticals [20][21][22][23], and other organic pollutants [24] from aqueous systems.…”
Section: Introductionmentioning
confidence: 99%
“…It can be also used in filtering bags in the river runoff. [42,76,[81][82][83][84][85] Animal husbandry -Supplements feed for ruminants (cattle and goats), pigs, poultry (chicken and duck), and fish. -Improves ruminal fermentation and feed efficiency.…”
Section: Potential Applications Of Biochar In the Neamentioning
confidence: 99%
“…However, this would require transport and would lead to the transfer of carbon and nutrients between regions. Biochar can also be used as filtering media in environmental remediation processes of contaminated drinking water or sewage [42,76,81,84]. Thus, the production of biochar in farmers' cooperatives can be a contribution to the efficient and sustainable use of water resources.…”
Section: Potential Applications Of Biochar In the Neamentioning
confidence: 99%
“…A very promising application of biochar is related to its suitability to retain various pollutants from waters (Duwiejuah et al, 2020; Inyang et al, 2016; Krasucka et al, 2021; Liu et al, 2021; Shakoor et al, 2020; Sizmur et al, 2017). Among the wide variety of pollutants, hexavalent chromium is by far one of the most toxic pollutants, representing the main threat to living organisms, including humans (Rowbotham et al, 2000).…”
Section: Introductionmentioning
confidence: 99%